Accuracy of ACR-TIRADS in assessment and diagnosis of thyroid nodules in patients underwent thyroid surgery in Taksin Hospital - Chainamnan, Worawan (Chulalongkorn Medical Journal, 2023)
Background: Ultrasound is generally considered most suitable to evaluate thyroid nodule sonographic morphology. The ultrasound-based risk stratification systems have been used to assess the probability of cancer in thyroid nodules. Objective: To determine the efficacy of ultrasound-based American College of Radiology Thyroid Imaging Reporting and Data System (ACR-TIRADS) in estimating the risk of malignancy in thyroid nodules in Thailand. Methods: A descriptive retrospective cross-sectional study was conducted at Taksin Hospital. In total, 324 patients with thyroid nodules underwent sonography and surgery; their pathological diagnoses were available, from January 2008 to April 2022. The ACR-TIRADS and ultrasound features were used to determine the risk of malignancy of thyroid nodules by using surgical histologic pathology from the tissue as the gold standard. Results: Of the 324 cases, 276 females (85.2%) and 48 males (14.8%) were eligible for inclusion. The risk of malignancy in thyroid nodules according to ACR-TIRADS had a sensitivity of 94.8%, specificity of 79.3%, positive predictive value (PPV) of 50.0%, negative predictive value (NPV) of 98.6%, and accuracy of 82.1%. The ultrasound findings with high malignancy risks were extra-thyroidal extension, lobulated or irregular margin, taller-than-wide shape, very hypoechoic, punctate echogenic foci and enlarged cervical lymph nodes. Conclusion: The ultrasound scoring-based ACR-TIRADS is a good indicator for evaluating cancer risk of thyroid nodules, determining further management, and reducing unnecessary thyroid biopsies.